Islamic Education for Children with Special Needs in an Inclusive Nonformal Education Setting - Ratnawati, Siti Rohmaturrosyidah (IAIN Ponorogo, 2022)
This study aims to explore the Islamic education programs for children with special needs and their implementation in nonformal institutions. The setting of this study was one of the orphanages in Ponorogo. It was Panti Asuhan Tunanetra Terpadu ”˜Aisyiyah Ponorogo. This study used a qualitative research approach. It was a case study research. The data were collected through interviews, observation, and documentation techniques. This study revealed that the Islamic education programs at this nonformal institution were divided into two categories. They were academic and non-academic education programs. The programs at this orphanage employed an inclusive approach by involving regular and special needs students in an education scope. It showed that the institution has tried to present an inclusive and friendly Islamic education milieu for children with special needs to fulfill their right to obtain a good education in religion and skill. Hence, they have equal opportunities to develop all their potential.